The Impact of Training Courses Implemented By International Organizations and Their Impact on The Performance of Agricultural Staff in Anbar - Saleh, Jasim (SAFE-Network, 2023)
Training has become a clear feature of developing the performance of institutions, and keeping pace with the rapid developments in all fields. The study aimed to determine the effect of training courses, which were implemented by international organizations, operating in province of Anbar, on the performance of agricultural employees. The study included workers in the agricultural departments in Anbar Governorate, numbering (136 employees). The questionnaire was designed to match the benefits of training and employee performance, and the Spss statistical program was used, with the use of Model: Patrick Kirk for the American expert. The results showed that the best resource for employees was through training courses, with an average score of 2.54, and in the field of orientation for training, use your training results when you return to our departments came first with an average of 2.71, and in terms of performance, decision making with averaged 3.93. The study indicated the positive relationship of performance with the educational level, the number of training courses, and the attitude towards training at a significant level of 0.01. The training depends on determining the training needs of the employee. in addition to the needs of the institution and the department in which he works, the need for the training to be in a timely manner, before the planting season and for the place to be suitable for the trainees, with the selection of the competent trainer with modern and developed information.